Cement paste with high bonding strength and low density as well as preparation method and application of cement paste
By reasonably preparing components, high cement strength and low-density cement slurry with a density of 1.30-1.70g/cm3 was prepared, which solved the problem of poor cementing effect of medium and low pressure leakage-prone wells in the prior art, and achieved efficient and low-cost cementing effect.
Patent Information
- Application Number
- CN202411790847.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
AI Technical Summary
The existing low-density cement slurry has poor cementing effect in low-pressure easily leaky wells, poor pressure resistance, complex operation and high cost, making it difficult to meet the cementing needs of low-pressure easily leaky layers.
By reasonably preparing components such as G-grade cement, modified perlite mitigator, microsilicon, water loss reducing agent, drag reducing agent, resin emulsion, retarder and defoaming agent in cement slurry, adjusting the slurry density and cement strength, high-cement strength and low-density cement slurry with a density of 1.30-1.70g/cm3 were prepared.
The density range and cementing capacity of cement slurry are improved, the compressive strength and cementing strength of cement stone are enhanced, the permeability of cement stone is reduced, the cementing quality and one-time success rate are improved, and the application cost is reduced.
Smart Images

Figure BDA0005175279000000131 
Figure BDA0005175279000000141 
Figure BDA0005175279000000142
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-density cementing for leak-prone wells, and in particular to a cement slurry with high bonding strength and low density, and a preparation method and application thereof. Background Art
[0002] With the acceleration of exploration and development, the development of oil and gas has moved from domestic to international. There are a large number of low-pressure and leaky wells in the Iraqi block. Low-density cement slurry system is the main method to solve the problem of cementing low-pressure and leaky formations. However, conventional low-density cement slurry lightening materials such as fly ash, microsilicon, bentonite, slag, etc. have limited ability to reduce the density of cement slurry; nitrogen and ordinary floating beads low-density cement slurry systems have poor pressure resistance and complex operation; hollow glass microbead cement slurry systems have high costs and cannot be promoted. Therefore, a low-cost, easy-to-operate low-density cement slurry system is needed to solve the one-time return problem of cementing low-pressure and leaky formations in this block. Summary of the invention
[0003] In view of this, the main purpose of the present invention is to provide a cement slurry with high bonding strength and low density and a preparation method and application thereof. The problem to be solved is to improve the density range of the cement slurry and the bonding ability of cement stone by matching various materials without affecting other properties of the slurry. The density of the cement slurry is 1.30-1.70 g / cm 3 The bonding strength of cement is increased by 50-100% compared with ordinary low-density cement.
[0004] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a high bonding strength and low density cement slurry, which is composed of the following components by weight: 100 parts of G-grade cement; 5-40 parts of lightening agent; 1-15 parts of microsilicon; 1-5 parts of fluid loss additive; 0.5-5 parts of drag reducer; 1-5 parts of resin emulsion; 0.1-2 parts of retarder; 0.1-0.2 parts of defoamer; 50-120 parts of water.
[0005] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0006] Preferably, in the aforementioned high bonding strength, low density cement slurry, the lightening agent is a modified perlite lightening agent.
[0007] Preferably, in the aforementioned high bonding strength and low density cement slurry, the microsilica is silicon dioxide powder with a purity of ≥98%, and the particle size of the silicon dioxide powder is 0.1 μm-0.3 μm.
[0008] Preferably, in the aforementioned high bonding strength, low density cement slurry, the modified perlite lightener has closed pores, a honeycomb structure inside, and a microbead-type hollow spherical powder in appearance. The color is off-white and the particle size is between 0.05-0.40 mm.
[0009] Preferably, in the aforementioned high bonding strength and low density cement slurry, the fluid loss reducer is selected from one of methylpropane sulfonic acid polymers and modified fibers.
[0010] Preferably, in the aforementioned high bonding strength and low density cement slurry, the fluid loss reducer is a methylpropane sulfonic acid polymer; in terms of mass percentage, the methylpropane sulfonic acid polymer includes 25-35% sodium polyacrylate and 65-75% 2-acrylamido-2-methylpropane sulfonic acid.
[0011] Preferably, in the aforementioned high bonding strength, low density cement slurry, the drag reducer is selected from one of aliphatic hydroxy sulfonate condensates, lignin sulfonates and naphthalene series.
[0012] Preferably, in the aforementioned cement slurry with high bonding strength and low density, the modified resin emulsion is a water-soluble modified resin, which is a gray viscous liquid; the density of the water-soluble modified resin is 1.15±0.05 g / cm 3 , viscosity ≤100 m Pa.s; the composition of the water-soluble modified resin in terms of mass percentage is: 90-92% of water-soluble epoxy resin; 8-10% of water.
[0013] Preferably, in the aforementioned high bonding strength, low density cement slurry, the retarder is selected from at least one of a high molecular polymer retarder, a lignin sulfonate retarder and an organic acid salt retarder.
[0014] Preferably, in the aforementioned high bonding strength, low density cement slurry, the defoaming agent is selected from at least one of tributyl phosphate, silicones and polyethers.
[0015] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0016] S1: 100 parts of oil well G grade cement, 5-40 parts of lightening agent and 1-15 parts of microsilica are mixed and stirred uniformly to prepare a dry mixed material;
[0017] S2: 50-120 parts of tap water, 1-5 parts of fluid loss additive, 0.5-5 parts of drag reducer, 0.1-2 parts of retarder, 1-5 parts of resin emulsion and 0.1-0.2 parts of defoamer are added and mixed and stirred uniformly to prepare a wet mixed material;
[0018] S3 stirs the wet mixed material obtained in step S2 at a speed of 3800-4200 r / min. While stirring, the dry mixed material obtained in step S1 is uniformly added to the wet mixed material, and then stirred at a speed of 3800-4200 r / min for 30-40 seconds. Finally, the high bonding strength and low density cement slurry is obtained after defoaming at 500-3000 r / min.
[0019] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0020] Preferably, in the above-mentioned method for preparing cement slurry with high bonding strength and low density, the modified perlite lightener is prepared by the following steps:
[0021] The Henan perlite ore is heated at a rate of 10-20°C / min to a target temperature of 1190-1210°C in 1-2 hours, and is roasted at 1190-1210°C for 3-5 hours. The temperature and the material residence time are controlled to a residence time of 2-4 hours to obtain the modified perlite lightener.
[0022] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a high bonding strength, low density cement slurry for use in low pressure wells and low pressure leaking wells. The use temperature range of the cement slurry is 20-120°C, and the density of the cement slurry is 1.30-1.70 g / cm 3 , bottom hole pressure ≤40 MPa.
[0023] By means of the above technical solution, the present invention provides a cement slurry with high bonding strength and low density and a preparation method and application thereof, which have at least the following advantages:
[0024] 1. The present invention determines the application scope of perlite lightener through experiments, combines with resin emulsion, reduces the application cost of low-density cement slurry system, improves the compressive strength of low-density cement stone, reduces the permeability of cement stone, improves the bonding strength of cement sheath, and improves the cementing quality of single well.
[0025] 2. The present invention can effectively improve the one-time success rate of cementing low-pressure and leak-prone layers, improve the bonding strength between cement stone and the formation and casing, and improve the quality of top cementing.
[0026] 3. The use temperature range of the cement slurry of the present invention is 20-120°C, and the density of the cement slurry is 1.30-1.70 g / cm 3 , bottom hole pressure ≤40 MPa, ensuring cement slurry return height and cementing quality of low-pressure wells and low-pressure wells prone to leakage.
[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0028] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a high bonding strength, low density cement slurry and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0029] The following materials or reagents, unless otherwise specified, were commercially available.
[0030] Some embodiments of the present invention provide a cement slurry with high bonding strength and low density, which is composed of the following components by weight: 100 parts of G-grade cement; 5-40 parts of lightener; 1-15 parts of microsilica; 1-5 parts of fluid loss additive; 0.5-5 parts of drag reducer; 1-5 parts of resin emulsion; 0.1-2 parts of retarder; 0.1-0.2 parts of defoamer; and 50-120 parts of water.
[0031] Taking into account the industry standard "GB10238 Oil Well Cement", the G-grade cement selects G-grade high-resistance cement.
[0032] The role of the lightening agent is to reduce the density of the 3 ) is used to reduce the density of cement slurry. According to experimental tests, when the amount added is less than 5 parts, the density of cement slurry does not decrease significantly. When the amount added is more than 40 parts, the slurry is difficult to deposit, the lightening agent is easy to float, the slurry is unstable, and the compressive strength is low.
[0033] Microsilicon is an ultrafine material. With its small particle size, large specific surface area and low cost, it can be used as a filler in cement slurry. It is filled between cement particles and lightener particles to increase the viscosity, high-temperature stability and density of cement paste, and reduce the permeability of cement paste. When the amount of microsilicon added is less than 1 part, the slurry stability is poor, the lightener is easy to float, and the compressive strength is low. When the amount of microsilicon added is more than 15 parts, the slurry density is high, and the amount of lightener needs to be greatly increased, which increases the overall cost of cement slurry.
[0034] The fluid loss reducer in cement slurry mainly reduces the filtration loss of cement slurry into the formation and reduces the pollution to the reservoir. When the amount added is less than 1 part, the cement slurry is easy to dehydrate, the slurry fluidity is poor, and cementing accidents are prone to occur. When the amount added is more than 5 parts, the slurry viscosity increases, the ash is difficult to deposit, and the thickening time and compressive strength will be affected to a certain extent.
[0035] The drag reducer plays a role in reducing the viscosity of cement slurry. When its addition amount is less than 0.5 parts, the viscosity reduction of the slurry is not obvious. When its addition amount is more than 5 parts, the viscosity of the cement slurry is too low, and stratification and sedimentation are prone to occur, which seriously affects the high-temperature stability of the cement slurry.
[0036] The resin emulsion mainly improves the bonding strength between the cement ring and the two interfaces, and helps reduce water loss. When its addition amount is less than 1, the increase in the bonding strength of the cement stone is not obvious. When its addition amount is more than 5 parts, the viscosity of the cement slurry is too large, making it difficult to lay the ash, increasing the cost of slurry application, and is not conducive to on-site construction application.
[0037] The retarder prolongs the thickening time in cement slurry. When the amount added is less than 0.1 parts, the thickening time of cement slurry is too short, which cannot meet the construction requirements and there are construction risks. When the amount added is more than 2 parts, the thickening time of cement slurry is too long, which is not conducive to the development of compressive strength. The on-site waiting time is extended, the construction period is increased, and the overall project effectiveness is affected.
[0038] Defoaming agent plays a role in defoaming in cement slurry. When its addition amount is less than 0.1 parts, it cannot effectively remove bubbles in cement slurry, affecting the determination of the true density of cement slurry. When its addition amount is greater than 0.2 parts, it affects the thickening time of cement slurry and increases the overall cost of the system.
[0039] In some optional embodiments, the G-grade cement may be a silicate-sulphoaluminate composite cement system.
[0040] In some optional embodiments, the lightening agent can be a modified perlite lightening agent, using Henan perlite ore, which includes 68-74% silicon dioxide and 26-32% aluminum oxide by mass percentage; the Henan perlite ore is heated at a rate of 10-20°C / min, and the temperature is raised to a target temperature of 1190-1210°C in 1-2 hours, and roasted at a high temperature of 1190-1210°C (the melting temperature of the perlite ore is 1200°C. When the target temperature is lower than 1190°C, the perlite ore cannot be completely melted and the expected production effect cannot be achieved. When the target temperature is higher than 1210°C, the requirements for equipment are higher, the production efficiency is reduced, and the production cost is increased). 3-5 hours (the roasting time must be sufficient to ensure that the temperature of all ores is uniform, and the roasting time below 3 hours If all the ores cannot be completely melted, the temperature cannot be stable and uniform, and if the roasting time is longer than 5 hours, the production time and production cost will be increased). By controlling the temperature and the material residence time (the ore is melted and then kept in the air so that it comes into contact with the air), the residence time is 2 to 4 hours (the residence time is determined according to the equipment parameters. If the residence time is less than 2 hours, the particle size and density of the product produced by the residence time cannot meet the design requirements. If the residence time is longer than 4 hours, the production time is increased, the product performance is not improved, the production cost of the product is increased, and the production time is reduced). The product surface is melted, the pores are closed, and the interior is a honeycomb structure. It is a tiny hollow spherical powder substance with the appearance of a microbead. The product has an off-white appearance, good dispersibility and fluidity, and the product particle size is between 0.05 and 0.40 mm.
[0041] In some optional embodiments, the microsilicon is a silicon dioxide powder with a purity of ≥98%, and the particle size of the silicon dioxide powder is 0.1μm-0.3μm. Microsilicon mainly plays a role of suspension and filling in cement slurry due to its small fineness and large specific surface area. When the particle size of microsilicon is less than 0.1 micron, the product needs to improve the production process, resulting in increased production costs and increased use costs, which is not conducive to the promotion and application of the product; when the particle size of microsilicon is greater than 0.3 micron, the amount of product used will increase, and the large particle size cannot achieve a good filling effect, which is not conducive to reducing the permeability of cement stone.
[0042] In some optional embodiments, considering the adaptability of the fluid loss agent, the fluid loss agent can be selected from one of methylpropane sulfonic acid polymers and modified fibers. In specific implementation, the fluid loss agent can be a copolymer of sodium polyacrylate and 2-acrylamide-2-methylpropane sulfonic acid; in terms of mass percentage, the methylpropane sulfonic acid polymer includes: 25-35% sodium polyacrylate; 65-75% 2-acrylamide-2-methylpropane sulfonic acid. When the content of sodium acrylate is lower than 25% and the content of 2-acrylamide-2-methylpropane sulfonic acid is higher than 75%, the generated polymer has a strong retarding effect, a long thickening time, and is not conducive to the development of the compressive strength of the cement slurry. When the content of sodium acrylate is higher than 35% and the content of 2-acrylamide-2-methylpropane sulfonic acid is lower than 65%, the generated polymer has a poor ability to control water loss, a high content, and a high overall cost of the cement slurry system.
[0043] In some optional embodiments, the drag reducer may be selected from one of aliphatic hydroxysulfonate condensates, lignin sulfonates and naphthalene series.
[0044] In some optional embodiments, the modified resin emulsion may be a water-soluble modified resin, which is a gray viscous liquid; the density of the water-soluble modified resin is 1.15±0.05 g / cm 3 , viscosity ≤100 m Pa.s; its composition by mass percentage is: 90-92% water-soluble epoxy resin; 8-10% water.
[0045] In some optional embodiments, the retarder may be selected from at least one of a high molecular weight polymer retarder, a lignin sulfonate retarder and an organic acid salt retarder.
[0046] In some optional embodiments, the defoaming agent may be selected from at least one of tributyl phosphate, silicones and polyethers.
[0047] In the above technical scheme, the present invention determines the use range of perlite lightener through experiments, combines with resin emulsion, reduces the application cost of low-density cement slurry system, improves the compressive strength of low-density cement stone, reduces the permeability of cement stone, improves the bonding strength of cement sheath, and improves the cementing quality of single well.
[0048] Some embodiments of the present invention also provide a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0049] S1: 100 parts of oil well G grade cement, 5-40 parts of lightening agent and 1-15 parts of microsilica are mixed and stirred uniformly to prepare a dry mixed material;
[0050] S2: 50-120 parts of tap water, 1-5 parts of fluid loss additive, 0.5-5 parts of drag reducer, 0.1-2 parts of retarder, 1-5 parts of resin emulsion and 0.1-0.2 parts of defoamer are added and mixed and stirred uniformly to prepare a wet mixed material;
[0051] S3 stirs the wet mixed material at a speed of 3800-4200r / min (preparation method determined according to industry standard GB19139), while stirring, add the dry mixed material to the wet mixed material at a uniform speed, and then stir at a speed of 3800-4200r / min (because the lightener is a hollow sphere, when the speed is less than 3800r / min, the slurry is not mixed evenly, and when the speed is greater than 4200r / min, part of the lightener is easily broken) for 30-40 seconds (determined according to industry standard GB19139), and finally defoam at a speed of 500-3000r / min to obtain the cement slurry with high bonding strength and low density. Since the defoaming process needs to be combined with the consistency of the cement slurry, the speed is less than 500r / min, and the speed is too low to stir the slurry; the speed is greater than 3000r / min, and the speed is too high to easily bring air into the cement slurry, and the purpose of defoaming cannot be achieved.
[0052] Some embodiments of the present invention also provide an application of a high bonding strength, low density cement slurry in cementing low pressure wells and low pressure leaking wells, wherein the use temperature range of the cement slurry is 20-120°C, the bottom hole pressure is ≤40 MPa, and the cement slurry density is 130-1.70 g / cm 3 , ensuring the cement slurry return height and cementing quality of low-pressure wells and low-pressure wells prone to leakage.
[0053] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0054] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0055] Example 1
[0056] This embodiment provides a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0057] Weigh 100 parts of oil well G grade cement, 5 parts of perlite lightener, and 5 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0058] Weigh 51 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 1 part of sodium gluconate, 2 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances evenly to prepare a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0059] The wet mixed material is stirred at a speed of 4000 r / min. While stirring, the dry mixed material is uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds. Finally, the high bonding strength and low density cement slurry is obtained after defoaming at 600 r / min.
[0060] The properties of the above cement slurry were measured and the measurement results are shown in Table 2.
[0061] Example 2
[0062] This embodiment provides a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0063] Weigh 100 parts of oil well G grade cement, 10 parts of perlite lightener, and 5 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0064] Weigh 53 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.4 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances to obtain a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0065] The wet mixed material is stirred at a speed of 4000 r / min. While stirring, the dry mixed material is uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds. Finally, the high bonding strength and low density cement slurry is obtained after defoaming at 600 r / min.
[0066] The properties of the above cement slurry were measured and the measurement results are shown in Table 2.
[0067] Example 3
[0068] This embodiment provides a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0069] Weigh 100 parts of oil well G grade cement, 15 parts of perlite lightener, and 6 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0070] Weigh 58 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 0.5 parts of aliphatic hydroxysulfonate condensate, 0.3 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances to obtain a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0071] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 680 r / min to obtain low-cost, high-bonding strength, low-density cement slurry. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0072] Example 4
[0073] This embodiment provides a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0074] Weigh 100 parts of oil well G grade cement, 25 parts of perlite lightener, and 6 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0075] Weigh 59 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.2 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances evenly to prepare a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0076] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 680 r / min to obtain the cement slurry with high bonding strength and low density. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0077] Example 5
[0078] This embodiment provides a method for preparing a cement slurry with high bonding strength and low density, comprising the following steps:
[0079] Weigh 100 parts of oil well G grade cement, 35 parts of perlite lightener, and 12 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0080] Weigh 67 parts of water, add 5 parts of methylpropane sulfonic acid polymer, 0.8 parts of aliphatic hydroxysulfonate condensate, 0.2 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances to obtain a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0081] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 660 r / min to obtain the cement slurry with high bonding strength and low density. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0082] Comparative Example 1
[0083] This comparative example provides a method for preparing cement slurry, comprising the following steps:
[0084] Weigh 100 parts of oil well G grade cement, 10 parts of perlite lightener, and 5 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0085] Weigh 53 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.4 parts of sodium gluconate, 0 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances evenly to prepare a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0086] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 640 r / min to obtain the cement slurry. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0087] Comparative Example 2
[0088] This comparative example provides a method for preparing cement slurry, comprising the following steps:
[0089] Weigh 100 parts of oil well G grade cement, 10 parts of power plant floating beads, and 5 parts of silicon dioxide powder (purity of 98%, particle size of 0.2μm), mix and stir the above substances evenly to prepare a dry mixed material; the power plant floating beads are a by-product of power plants, and the number of products is decreasing year by year. The unit price of power plant floating beads is high, about 3 times that of perlite lightener. The use of other lightener products such as fly ash and bentonite has a large addition amount, and the cement slurry density can only be reduced to 1.60g / cm 3 about;
[0090] Take 53 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.4 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances evenly to prepare a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamide-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0091] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 600 r / min to obtain the cement slurry. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0092] Comparative Example 3
[0093] This comparative example provides a method for preparing cement slurry, comprising the following steps:
[0094] Weigh 100 parts of oil well G grade cement, 0 parts of perlite lightener, and 15 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0095] Weigh 88 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.4 parts of sodium gluconate, 3 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances to obtain a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0096] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 600 r / min to obtain the cement slurry with high bonding strength and low density. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0097] Comparative Example 4
[0098] This comparative example provides a method for preparing cement slurry, comprising the following steps:
[0099] Weigh 100 parts of oil well G grade cement, 25 parts of perlite lightener, and 12 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances to obtain a dry mixed material; the modified perlite lightener includes 70% silicon dioxide and 30% aluminum oxide by mass percentage; the modified perlite lightener is a hollow spherical powder with closed pores, a honeycomb structure inside, and a microbead-type appearance, with a grayish white color and a particle size of 0.125 mm; the modified perlite lightener is obtained by the following steps: heating the Henan perlite mine at a rate of 13°C / min, raising it to a target temperature of 1200°C in 1.5 hours, and roasting it at 1200°C for 4 hours, and controlling the temperature and the material residence time, with the residence time being 3 hours, to obtain the modified perlite lightener.
[0100] Weigh 67 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.2 parts of sodium gluconate, 0 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances to obtain a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamido-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15 g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0101] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 600 r / min to obtain the cement slurry with high bonding strength and low density. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0102] Comparative Example 5
[0103] This comparative example provides a method for preparing cement slurry, comprising the following steps:
[0104] Weigh 100 parts of oil well G grade cement, 10 parts of power plant floating beads, and 5 parts of silicon dioxide powder (purity of 98%, particle size of 0.2 μm), mix and stir the above substances evenly to prepare a dry mixed material; the power plant floating beads are a byproduct of the power plant;
[0105] Take 50 parts of water, add 4 parts of methylpropane sulfonic acid polymer, 1 part of aliphatic hydroxysulfonate condensate, 0.4 parts of sodium gluconate, 0 parts of water-soluble modified resin, and 0.2 parts of tributyl phosphate, mix and stir the above substances evenly to prepare a wet mixed material; the methylpropane sulfonic acid polymer includes, by mass percentage, 30% of sodium polyacrylate and 70% of 2-acrylamide-2-methylpropane sulfonic acid; the water-soluble modified resin is a gray viscous liquid with a density of 1.15g / cm 3 , viscosity 80 m Pa.s; its composition by mass percentage is: 90wt% water-soluble epoxy resin; 10wt% water;
[0106] The wet mixed material was stirred at a speed of 4000 r / min, and while stirring, the dry mixed material was uniformly added to the wet mixed material, and then stirred at a speed of 4000 r / min for 35 seconds, and finally defoamed at 600 r / min to obtain the cement slurry. The properties of the cement slurry were measured, and the measurement results are shown in Table 2.
[0107] Table 1 Performance requirements of cement slurry prepared in Examples 1-5
[0108]
[0109]
[0110] Thickening time: The time required for water and cement to reach a consistency of 100 Bc after mixing.
[0111] The test procedures and methods for cement slurry performance testing refer to the national standard GB / T 19139-2012, and the cement slurry performance parameters refer to the industry standard SY / T 6544-2017.
[0112] Table 2 Performance test results of cement slurries with high bonding strength and low density in Examples 1-5 and cement slurries in Comparative Examples 1-5
[0113]
[0114]
[0115] Note: The cement slurry performance test method refers to the national standard GB / T 19139-2012, the bonding strength refers to the utility model patent "Cementing Interface Bonding Strength Test Device", and the cement slurry performance parameters refer to the industry standard SY / T6544-2017.
[0116] It can be seen from the data of Examples 1-5 that the high bonding strength and low density cement slurry needs to be combined with the addition of lightener, microsilicon, resin emulsion, fluid loss reducer, drag reducer and retarder to adjust a set of cement slurry system with good slurry performance in all aspects. The low density cement slurry has a wide range of application, with a density of 1.30-1.70 g / cm 3 It can meet the cementing requirements of low-pressure and leak-prone layers in Iraq. The crushing rate of the lightener in the cement slurry is less than 5%, and the slurry density is relatively stable, which reduces the risk of pressure leakage in the formation during the construction process and improves the one-time success rate of cementing.
[0117] It can be seen from Example 2 and Comparative Example 1 that the bonding strength of cement slurry is significantly increased after adding resin emulsion. When the amount of resin added is zero, the 72-hour bonding strength is only 1.85 MPa, while after adding 2 parts of resin emulsion, the bonding strength is increased to 3.57 MPa, which is 1.93 times that of the system without resin emulsion. The increase in bonding strength is quite obvious, which is beneficial to the development of the bonding strength between the cement sheath and the two interfaces and improves the top cementing quality.
[0118] It can be seen from Example 2 and Comparative Example 3 that at 1.60 g / cm 3 The perlite lightening agent is removed from the low-density cement slurry, and the amount of resin emulsion remains unchanged. There is no lightening agent in the cement slurry, and the density is mainly reduced by water. Therefore, the water-cement ratio of the cement slurry is large, and the slurry is easy to configure, but the fluidity is large, the upper and lower density differences are large, and the free liquid is greater than 1.2% (the volume ratio of the upper precipitate of the cement slurry to the cement slurry in the stability test). The slurry is extremely unstable, and the compressive strength and bonding strength are both low, which does not meet the requirements of cementing construction.
[0119] It can be seen from Example 4 and Comparative Example 4 that at 1.40 g / cm 3 Resin emulsion was removed from the low-density cement slurry, and the amount of microsilicon was increased from 6 parts to 12 parts. The cement slurry was difficult to deposit, the perlite lightener floated significantly at high temperatures, the cement slurry was less stable, the difference in density between the upper and lower surfaces was large, and even cement stratification occurred. The 72-hour compressive strength and joint strength were both low, which could not meet the requirements of on-site construction.
[0120] From the perspective of the working principle of the lightener and the resin emulsion, the perlite lightener has the characteristics of low density and large particle size, which can reduce the density of cement slurry. However, when the density of cement slurry is lower than 1.50g / cm 3When adding perlite lightener, the amount of water-cement ratio of cement paste is large, the stability of the paste is poor, and even if a large amount of micro-silicon is added, it is difficult to solve the contradiction between ash release and stability. Resin emulsion is a nano-scale liquid material with a finer particle size than micro-silicon. It can solve the ash release problem and fill between micro-silicon, perlite lightener and cement particles, improve the stability of cement paste, reduce the permeability of cement paste, and improve the compressive strength of cement paste.
[0121] By comparing the data of Example 2 with Comparative Example 2, it can be seen that the performance of the low-density cement slurry configured with the same type of lightening agent power plant floating beads is basically different from that of the cement slurry prepared with perlite lightening agent, and its crushing rate is higher, the crushing is greater than 5%, up to 7%, which is not conducive to the cementing of low-pressure and leak-off layers, and the compressive strength and bonding strength are reduced by more than 50% compared with Example 2, and there is a risk of pressure leakage and poor bonding during the cementing process. Moreover, the price of power plant floating beads is three times that of perlite lightening agent, which increases the cost of the cement slurry system and is not conducive to the application of low-cost projects abroad.
[0122] By comparing the data of Example 2 with that of Comparative Example 5, it can be seen that Comparative Example 5 is a common low-density cement slurry, the amount of lightener and microsilicon added is the same, and no resin emulsion is added. The slurry density is relatively high (1.62 g / cm 3 ), the 72-hour compressive strength and bonding strength of Example 2 of the present invention are improved by about 100% compared with the ordinary low-density system.
[0123] In summary, the present invention provides a set of high bonding strength and low density cement slurry suitable for medium temperature. The cement slurry has a simple formula, a small amount of resin emulsion, and a significantly improved bonding strength of cement stone, which is twice that of ordinary cement stone. The cement stone has high compressive strength, 72-hour compressive strength>12MPa, API filtration loss<50 ml, the slurry is stable at high temperature without free liquid, the thickening time is adjustable, etc. It is easy to operate in field application, is one-third of the price of similar products, and has low application cost.
[0124] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0125] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0126] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A cement slurry with high bonding strength and low density, characterized in that: The invention is composed of the following components by weight: 100 parts of G-grade cement; 5-40 parts of lightening agent; 1-15 parts of microsilica; 1-5 parts of fluid loss reducer; 0.5-5 parts of drag reducer; 1-5 parts of resin emulsion; 0.1-2 parts of retarder; 0.1-0.2 parts of defoaming agent; and 50-120 parts of water.
2. The high bonding strength, low density cement slurry according to claim 1, characterized in that: The lightening agent is a modified perlite lightening agent; the microsilicon is silicon dioxide powder with a purity of ≥98%, and the particle size of the silicon dioxide powder is 0.1 μm-0.3 μm.
3. The high bonding strength, low density cement slurry according to claim 2, characterized in that: The modified perlite lightener has closed pores, a honeycomb structure inside, and a microbead-shaped hollow spherical powder in appearance. The color is off-white and the particle size is between 0.05 and 0.40 mm.
4. The high bonding strength, low density cement slurry according to claim 1, characterized in that: The fluid loss reducer is selected from one of methylpropane sulfonic acid polymers and modified fibers.
5. The high bonding strength, low density cement slurry according to claim 4, characterized in that: The fluid loss reducer is a methylpropane sulfonic acid polymer; in terms of mass percentage, the methylpropane sulfonic acid polymer comprises 25-35% of sodium polyacrylate and 65-75% of 2-acrylamide-2-methylpropane sulfonic acid.
6. The high bonding strength, low density cement slurry according to claim 1, characterized in that: The drag reducer is selected from aliphatic hydroxysulfonate condensates, lignin sulfonates and naphthalene series; the resin emulsion is a water-soluble modified resin, which is a gray viscous liquid; the density of the water-soluble modified resin is 1.15±0.05g / cm 3 , viscosity ≤100 m Pa.s; the composition of the water-soluble modified resin in terms of mass percentage is: 90-92% of water-soluble epoxy resin; 8-10% of water.
7. The high bonding strength, low density cement slurry according to claim 1, characterized in that: The retarder is selected from at least one of high molecular polymer retarders, lignin sulfonate retarders and organic acid salt retarders; the defoamer is selected from at least one of tributyl phosphate, silicone and polyether.
8. A method for preparing cement slurry with high bonding strength and low density, characterized in that: The following steps are involved: S1: 100 parts of oil well G grade cement, 5-40 parts of lightening agent and 1-15 parts of microsilica are mixed and stirred uniformly to prepare a dry mixed material; S2: 50-120 parts of water, 1-5 parts of fluid loss additive, 0.5-5 parts of drag reducer, 0.1-2 parts of retarder, 1-5 parts of resin emulsion and 0.1-0.2 parts of defoamer are mixed and stirred uniformly to prepare a wet mixed material; S3 stirs the wet mixed material obtained in step S2 at a speed of 3800-4200 r / min. While stirring, the dry mixed material obtained in step S1 is uniformly added to the wet mixed material, and then stirred at a speed of 3800-4200 r / min for 30-40 seconds. Finally, the high bonding strength and low density cement slurry is obtained after defoaming at 500-3000 r / min.
9. The method for preparing cement slurry with high bonding strength and low density according to claim 8, characterized in that: The modified pearlite lightener is prepared by the following steps: The Henan perlite ore is heated at a rate of 10-20°C / min to a target temperature of 1190-1210°C in 1-2 hours, and is roasted at 1190-1210°C for 3-5 hours. The temperature and the material residence time are controlled to a residence time of 2-4 hours to obtain the modified perlite lightener.
10. Use of the high bonding strength and low density cement slurry according to any one of claims 1 to 7 in cementing low pressure wells and low pressure wells prone to leakage, characterized in that: The use temperature range of the cement slurry is 20-120°C, and the density of the cement slurry is 1.30-1.70 g / cm 3 , bottom hole pressure ≤40 MPa.